2018
DOI: 10.1029/2017jd028226
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes in Extreme Temperature and Precipitation Events in the Three‐Rivers Headwater Region, China

Abstract: Extreme climate events affect sustainable development in many parts of the world. Although several studies of local extreme climate events exist, such events need more thorough investigation. Detailed studies of climatic variations that assess changes on both spatial and temporal scales are becoming increasingly necessary. In this study, 14 indices for extreme temperature and 12 indices for extreme precipitation were used to analyze the spatial distribution and temporal trends of extreme climate events in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 76 publications
2
20
1
Order By: Relevance
“…The simulations of future scenarios by climate models show a decrease in the duration of mid-latitude precipitation extremes and changes in the zonal extent of both signs depending on latitude 12 . Observations confirm the changing temporal distribution of heavy rain events 1315 . The frequency and duration of rainstorms are increasing over the Indian landmass 16 .…”
Section: Introductionsupporting
confidence: 69%
“…The simulations of future scenarios by climate models show a decrease in the duration of mid-latitude precipitation extremes and changes in the zonal extent of both signs depending on latitude 12 . Observations confirm the changing temporal distribution of heavy rain events 1315 . The frequency and duration of rainstorms are increasing over the Indian landmass 16 .…”
Section: Introductionsupporting
confidence: 69%
“…We observe that there are no significant variations in annual precipitation after the year 1991 (the change-point year based on the M-K abrupt change test) ( Figure S1a), whereas for temperature, there are straightforward M-K variations for annual mean, minimum, and maximum temperatures ( Figure S1b-d). As compared with our previous research [41], the frequency of occurrence of daily precipitation of more than 10 mm showed an upward trend. At the same time, the amount of precipitation did not change greatly, which means that the occurrence of dry days also showed an upward trend.…”
Section: Temporal Pattern Of Long-term Observed Variablescontrasting
confidence: 44%
“…The atmospheric moisture content will increase accompanying with the increased water-holding capacity with warming (Karl & Trenberth, 2003;Soden et al, 2005) and consequently enhance extreme precipitation (O'Gorman & Schneider, 2009;Trenberth, 1999). Intensification of East Asian climate system, as well as the changes in Antarctic Oscillation, Arctic Oscillation, Indian Summer Monsoon, and North Atlantic Oscillation, have significant correlation with the increases in precipitation extremes over China (Chen, 2013;Chen et al, 2010;Gong et al, 2011;Sun et al, 2008;Sundaram et al, 2012;Tong et al, 2006;Xi et al, 2018;Zhao et al, 2012). Although increasing trend of extreme precipitation shows in both dry and wet regions, distinct difference exists between dry and wet regions.…”
Section: Discussionmentioning
confidence: 99%